2020
DOI: 10.1101/2020.03.31.20044255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome Wide Epistasis Study of On-Statin Cardiovascular Events with Iterative Feature Reduction and Selection

Abstract: Background Predicting risk for major adverse cardiovascular events (MACE) is an evidence-based practice that incorporates lifestyle, history, and other risk factors. Statins reduce risk for MACE by decreasing lipids, but it is difficult to stratify risk following initiation of a statin. Genetic risk determinants for on-statin MACE are low-effect size and impossible to generalize. Our objective was to determine high-level epistatic risk factors for on-statin MACE with GWAS-scale data. Methods Controlled-access … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The copyright holder for this preprint this version posted January 15, 2023. ; https://doi.org/10.1101/2023.01.12.523835 doi: bioRxiv preprint [5] and Alzheimer's Disease [6] from simulated and real-world GWAS-scale data. RF-based methodologies have also been designed to identify non-coding variants [7,8] and to predict rare variant pathogenicity [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted January 15, 2023. ; https://doi.org/10.1101/2023.01.12.523835 doi: bioRxiv preprint [5] and Alzheimer's Disease [6] from simulated and real-world GWAS-scale data. RF-based methodologies have also been designed to identify non-coding variants [7,8] and to predict rare variant pathogenicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Even though, to date, autoML packages specifically designed for phenotype to genotype association in omics level data have not been fully explored, there have been several significant and promising attempts. As initial examples, there have been studies that have identified epistatic interactions using random forest (RF) methodologies for major adverse cardiovascular events [5] and Alzheimer's Disease [6] from simulated and real-world GWAS-scale data. RF-based methodologies have also been designed to identify non-coding variants [7,8] and to predict rare variant pathogenicity [9].…”
Section: Introductionmentioning
confidence: 99%